Singaporean framework of antecedents and consequences of doing charity. - Mak, Lily Seok Ling. (2008)
Previous research had focused on altruistic versus egoistic motivations of prosocial behaviour in the Western context. This research aimed to uncover the different motivations and the resulting emotions of Singaporeans who engaged in charitable actions. A framework was developed through the identification of six motivational profiles and the predictions of resulting emotions of each profile.